Medical ethnobotany of the Albanian Alps in Kosovo - Mustafa Behxhet; Hajdari Avni; Krasniqi Feriz; Hoxha Esat; Ademi Hatixhe; Quave Cassandra L; Pieroni Andrea (BMC, 2012)
Abstract Background Ethnobotanical studies are crucial in South-Eastern Europe for fostering local development and also for investigating the dynamics of Traditional Environmental Knowledge (TEK) related to plants in one of the most crucial European hotspots for biocultural diversity. The current medico-ethnobotanical survey was conducted in rural alpine communities in Kosovo. The aims of the study were twofold: 1) to document the state of TEK of medicinal plants in these communities; 2) to compare these findings with that of similar field studies previously conducted among local populations inhabiting the Montenegrin and Albanian side of the same Alpine range. Methods Field research was conducted in 36 villages on the Kosovar side of the Albanian Alps. Snowball sampling techniques were used to recruit 91 elderly informants (≥ 50 years-old) for participation in semi-structured interviews and structured surveys regarding the use of the local flora for medicinal and food purposes. Standard ethnobotanical methods were employed and prior informed consent was obtained for all study participants. Results and Conclusion The uses of 98 plants species belonging to 39 families were recorded; the most quoted botanical families were Rosaceae, Asteraceae, and Lamiaceae. Mainly decoctions and infusions were quoted as folk medicinal preparations and the most common uses referred to gastrointestinal and respiratory disorders, as well as illnesses of the uro-genital system. Among the most uncommon medicinal taxa quoted by the informants, Carduus nutans L., Echinops bannaticus Rochel ex Schrad., and Orlaya grandiflora Hoffm. may merit phytochemical and phytopharmacological investigations. Comparison of the data with other ethnobotanical field studies recently conducted on the Albanian and Montenegrin sides of the same Alps has shown a remarkable link between the medical ethnobotany of Montenegrin and Kosovar side of the Albanian Alps. Moreover, folk uses of the most quoted wild medicinal taxa recorded in Kosovo often include those recorded both in Albania and in Montenegro, thus suggesting a hybrid character of the Kosovar local plant knowledge. This may be also explained with the fact that Montenegro and Kosovo, despite their differences in the ethnic composition, have shared a common history during the last Century.